Functional shifts in lake zooplankton communities with hypereutrophication. (17th January 2019) - Moody, Eric K.; Wilkinson, Grace M.
Abstract: Functional variation among consumer communities can alter ecosystem nutrient cycling. These impacts on ecosystem function can be specifically driven by interspecific variation in stoichiometric traits; thus, functional trait‐based approaches can be used to explain the processes controlling ecosystem stoichiometry. However, eutrophication may reduce the functional importance of consumers in ecosystems by eliminating heterogeneity in nutrient recycling among taxa. To test whether zooplankton functional diversity, i.e. aspects of the stoichiometric trait space occupied by zooplankton communities, varies over gradients in trophic state and nutrient stoichiometry, we examined functional and taxonomic variation in the zooplankton communities of 130 lakes in the agriculturally dominated state of Iowa (U.S.A.) over 7 years. Stoichiometric functional dispersion decreased with trophic state index, supporting the trait abundance shift hypothesis that hypereutrophic lakes are characterised by different combinations of functional traits than their less eutrophic counterparts. Zooplankton communities became increasingly N‐rich relative to P as TSI increased. Specifically, P‐poor Bosmina, Chydorus, and cyclopoid copepods increased in abundance with eutrophication. Stoichiometric trait distributions of zooplankton shift with eutrophication, which implies that the unique functioning of hypereutrophic lakes could be due in part to the consumers inhabiting them. As zooplankton N:P increased with trophic state while lake total nitrogen to total phosphorus ratio decreased with trophic state, P‐poor zooplankton taxa may exacerbate excess P availability in these hypereutrophic systems by differentially recycling P at higher rates.